1991
DOI: 10.1177/003693309103600107
|View full text |Cite
|
Sign up to set email alerts
|

Venous Bullet Embolism: A Complication of Airgun Pellet Injuries

Abstract: Bullet emboli are an interesting but rare occurrence and their management when situated in the venous system remains controversial. Two cases of venous bullet embolism to the right heart are reported due to airgun pellet injuries. Both cases required bullet embolectomy using cardio-pulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…Embolization by foreign body after a gunshot in the civilian setting is rare and the exact incidence is unknown. It is commoner in arteries (80%) than veins (20%) [6]. Drapanas T. et al [4] study showed that the majority of the patients with arterial injury have other associated injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization by foreign body after a gunshot in the civilian setting is rare and the exact incidence is unknown. It is commoner in arteries (80%) than veins (20%) [6]. Drapanas T. et al [4] study showed that the majority of the patients with arterial injury have other associated injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Bullet embolization can be arterial or venous, with most documented cases being arterial. [3] Arterial embolization typically originates from the large arteries, left ventricle, aorta, or pulmonary veins, and often embolizes to lower-extremity arteries. [4,5] Venous embolization frequently originates from the large peripheral veins or the vena cava, embolizing to the right side of the heart, particularly to the right ventricle or pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of a bullet lodging in the vascular system in penetrating trauma patients is *0.3 % [11]. Approximately, 80 % of foreign body or bullet emboli are arterial (systemic or pulmonary) [7] and the remaining emboli are venous [4].…”
Section: Discussionmentioning
confidence: 99%
“…Survival is contingent upon rapid diagnosis and treatment of major injuries [2]. Embolization of traumatic foreign bodies is even more uncommon [3][4][5][6][7][8][9][10][11][12][13]. Recently, we successfully treated a patient with penetrating cardiac trauma with embolization of a foreign body to the pulmonary circulation without major operative intervention.…”
Section: Introductionmentioning
confidence: 99%